(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
This monographic issue of "Storie di edizioni" was to have been presented at a seminar in May 2020: the spread of the Covid-19 virus made it impossible to hold the planned meeting, in which - together with the authors of the essays - Giulia Raboni (of the University of Parma) and Emilio Russo (of the University of Rome La Sapienza) were to have opened the proceedings with their reflections. We decided to involve the two scholars anyway, closing the online issue and sending it to print, inviting them to a conversation on the many topics that the history of editions can bring to the fore. The conversation - made possible thanks to their willingness - is offered here as an opening (and commentary) to the essays devoted to individual editions and their history.